Prognostic and predictive value of Immunoscore and its correlation with ctDNA in stage II colorectal cancer - Fulong Wang; Shixun Lu; Di Cao; Juanjuan Qian; Cong Li; Rongxin Zhang; Feng Wang; Miaoqing Wu; Yifan Liu; Zhizhong Pan; Xiaojun Wu; Zhenhai Lu; et al. (OncoImmunology)
This study aimed to validate the prognostic value of Immunoscore (IS) in stage II colorectal cancer (CRC), and explore the roles of IS and circulating tumor DNA (ctDNA) in the adjuvant treatment for early-stage CRC. Resected tumor samples from stage II CRC patients were collected from the Sun Yat-sen University Cancer Center. The densities of CD3+ and CD8+ lymphocytes were quantified and converted to IS and classified into Low, Intermediate (Int), and High groups according to predefined cutoffs. A total of 113 patients were included in the study. Patients with IS-High, Int, and Low were 43 (38%), 62 (55%), and 8 (7%), respectively. Patients with IS-High had an excellent clinical outcome, with none recurring during a median follow-up of 3 years, including 15 (35%) clinical high-risk patients. The 3-year disease-free survival (DFS) was 100% for IS-High, 76% for IS-Int, and 47% for IS-Low (P < .001). In the multivariate Cox analysis, IS was the only significant parameter associated with DFS. IS-Int and IS-Low patients with adjuvant chemotherapy had improved DFS compared to those who did not receive adjuvant chemotherapy (HR = 0.3; 95% CI 0.1–0.92; P = .026). Among the 49 patients with postoperative ctDNA data, IS-High patients had the lowest ctDNA positivity rate, suggesting that they were most eligible for chemotherapy-free treatment. IS had a strong prognostic value in Chinese patients with stage II CRC and demonstrates its clinical utility. IS and ctDNA will jointly optimize the adjuvant treatment strategies for early-stage CRC.